(untitled) (Communications in Mathematical Research, 2021)
Let E be a real uniformly convex and smooth Banach space, and K be a nonempty closed convex subset of E with P as a sunny nonexpansive retraction. Let T_1, T_2 : K → E be two weakly inward nonself asymptotically nonexpansive mappings with respect to P with a sequence {k^(i)_n} ⊂ [1, ∞) (i = 1, 2), and F := F(T_1) ∩ F(T_2) ≠ ∅. An iterative sequence for approximation common fixed points of the two nonself asymptotically nonexpansive mappings is discussed. If E also has a Fréchet differentiable norm or its dual E^∗ has Kadec-Klee property, then weak convergence theorems are obtained.